Potential of enhancing anti-obesogenic agriceuticals by applying sustainable fertilizers during plant cultivation - Guardiola-Márquez, Carlos Esteban; Jacobo-Velázquez, Daniel A. (Frontiers in Sustainable Food Systems, 2022)
Overweight and obesity are two of the world’s biggest health problems. They are associated with excessive fat accumulation resulting from an imbalance between energy consumed and energy expended. Conventional therapies for obesity commonly include synthetic drugs and surgical procedures that can lead to serious side effects. Therefore, developing effective, safe, and readily available new treatments to prevent and treat obesity is highly relevant. Many plant extracts have shown anti-obesogenic potential. These plant extracts are composed of different agriceuticals such as fibers, phenolic acids, flavonoids, anthocyanins, alkaloids, lignans, and proteins that can manage obesity by suppressing appetite, inhibiting digestive enzymes, reducing adipogenesis and lipogenesis, promoting lipolysis and thermogenesis, modulating gut microbiota and suppressing obesity-induced inflammation. These anti-obesogenic agriceuticals can be enhanced in plants during their cultivation by applying sustainable fertilization strategies, improving their capacity to fight the obesity pandemic. Biofertilization and nanofertilization are considered efficient, eco-friendly, and cost-effective strategies to enhance plant growth and development and increase the content of nutrients and bioactive compounds, representing an alternative to overproducing the anti-obesogenic agriceuticals of interest. However, further research is required to study the impact of anti-obesogenic plant species grown using these agricultural practices. This review presents the current scenario of overweight and obesity; recent research work describing different plant species with significant effects against obesity; and several reports exhibiting the potential of the biofertilization and nanofertilization practices to enhance the concentrations of bioactive molecules of anti-obesogenic plant species.